Toxicology Evaluation of Realgar-Containing Niu-Huang-Jie-Du Pian as Compared to Arsenicals in Cell Cultures and in Mice - Miao, Jia-Wei (International Scholarly Research Network, 2011)
Niu-Huang-Jie-Du Pian (NHJD) is a widely used traditional Chinese medicine containing realgar (As(4)S(4)). Realgar has been included in many traditional medicines, but is often taken as arsenite for risk assessment. To evaluate true risk of realgar and realgar-containing NHJD, their toxicity was compared with common arsenicals. In cultured cells, the LC(50) for NHJD (1200 μM) and realgar (2000 μM) was much higher than arsenite(35 μM), arsenic trioxide (280 μM), and arsenate (400 μM). Acute toxicity in mice showed more severe liver and kidney injury after arsenite or arsenate, but was mild after realgar and NHJD, corresponding to cellular and tissue arsenic accumulation. The expressions of arsenic-sensitive stress gene metallothionein-1 were increased 3–7-folds after arsenite or arsenate, but were unaltered after NHJD and realgar. Thus, realgar and NHJD are much less toxic than arsenite and arsenate. The use of total arsenic to evaluate the safety of realgar and realgar-containing NHJD is inappropriate.